PENINGKATAN KEMAMPUAN SOSIAL EMOSIONAL ANAK MELALUI METODE BERMAIN PERAN MAKRO DI KELOMPOK B PAUD CEMPAKA TEMPEL LELEA - Rohmalasarti; Irfan Fauzi Rahmat; M. Arif Syarif (Bunayya, 2026)
This study was motivated by the low level of social-emotional skills among Group B children at PAUD Cempaka Tempel Lelea, as indicated by their limited ability to cooperate, interact, communicate, and regulate emotions during learning activities. The purpose of this study was to improve children's social-emotional skills through the implementation of the macro role-playing method. The novelty of this research lies in the collaborative application of the macro role-playing method within a rural early childhood education setting to develop cooperation, social interaction, communication, and emotional regulation skills among young children. This study employed a Classroom Action Research (CAR) design conducted in two cycles involving 12 Group B children as research participants. Data were collected through observation and documentation techniques. The findings revealed a continuous improvement in children's social-emotional skills across each cycle. The percentage of mastery increased from 16.67% in the pre-cycle stage to 41.67% in Cycle I and reached 83.33% in Cycle II. Improvements were observed in children's ability to cooperate, interact with peers, communicate effectively, and regulate emotions during role-playing activities. It can therefore be concluded that the macro role-playing method is effective in enhancing the social-emotional skills of Group B children at PAUD Cempaka Tempel Lelea.